Mechanisms of plastic instability and fracture of compressed and tensile tested Mg-Li alloys investigated using the acoustic emission method (Fracture and Structural Integrity, 2015)
The results of the investigation of both mechanical and acoustic emission (AE) behaviors of Mg4Li5Al alloy subjected to compression and tensile tests at room temperature are compared with the test results obtained using the same alloy and loading scheme but at elevated temperatures. The main aim of the paper is to investigate, to determine and to explain the possible influence of factors related with enhanced internal stresses such as: segregation of precipitates along grain boundaries or solute atoms along dislocations (Cottrell atmospheres) or dislocation pile-ups at grain boundaries which create very high stress concentration leading to fracture. The results show that the plastic instabilities are related to the Portevin–Le Châtelier phenomenon (PL effect) and they are correlated with the generation of AE peaks. The fractography of breaking samples was analyzed on the basis of light (optical), TEM and SEM images.
Keywords: Lightweight Alloys; Acoustic Emission; Fracture; Portevin–Le Châtelier Phenomenon; Twinning; Dislocations; Shear Bands